The effectiveness of training mothers with Barclay's behavioral approach on the dimensions of parenting and anxiety of children with attention deficit/hyperactivity disorder - Yaghobiyan, Roghayeh; Ghandhari, Nasim (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Not only is it important to investigate the components and factors affecting it in order to help prevent and treat this disorder in children, but it is also necessary to investigate the effectiveness of effective treatments in reducing the symptoms of this disorder. The present study was conducted with the aim of determining the effectiveness of teaching mothers with Barclay's behavioral approach on the dimensions of parenting and anxiety of children with attention deficit/hyperactivity disorder. Methods: The research method was quasiexperimental with pre-test and post-test design with experimental and control groups. The research population was all children with attention deficit/hyperactivity disorder who referred to the specialized children's psychiatric clinic in Gorgan city in the first ten months of 2022. The research sample was 24 people who were selected by purposive sampling method and randomly assigned to three groups of experimental (n=12) and control (n=12). The experimental group received Barclay Behavioral Maternal Education in 12 sessions of 90 minutes. The research instruments were the Alabama Form Parent Parenting Questionnaire (1991), and Spence Form Parent Child Scale (2001). Data were analyzed by analysis of covariance using SPSS-22 software. Results: The results showed that parent training with Barclay's approach improved parenting dimensions (parental participation, positive parenting, instability in discipline, weakness in monitoring and physical punishment) in mothers and reduced anxiety in children with attention deficit/hyperactivity disorder (P